Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was trying to solve

$$\int_0^\infty x \exp \left( { - \frac{{{x^2}}}{2}} \right)\;{\text{d}}x$$

I was trying to use $$(f(g(x)))'=f'(g(x))\cdot g'(x)$$

(So $[e^{f(x)}]'=[e^{f(x)}]\cdot f'(x)$ ?), but I got the wrong answer. (I substituted $0$ and $\infty$ to $-\exp \left(-\frac{x^2}{2}\right)$ and got 1. But the test solution says $\sqrt{e}$.)

Could you point out what's wrong with my solution?

share|cite|improve this question
The book's answer is incorrect; your integral evaluates to $1$ – David Mitra Aug 21 '12 at 0:17
Nothing wrong with your answer. In the long run you may find the notation $u$, $\frac{du}{dx}$ more useful for integration by substitution. – André Nicolas Aug 21 '12 at 0:20
It should be noted that $*$ is often used to denote convolution of functions, rather than pointwise multiplication. If you do mean pointwise multiplication it is best to use $\cdot$ (\cdot) or remove the symbol altogether. – Asaf Karagila Aug 21 '12 at 0:22
@AsafKaragila I see. Thank you for your advice! – Tengu Aug 21 '12 at 0:34
@DavidMitra In that case, I may not have written the problem correctly. Actually the problem is A-3 Putnam exam in 1997. Here are the links for problem and the solution. – Tengu Aug 21 '12 at 0:38
up vote 1 down vote accepted

We know that

$$\int f'(g(x))g'(x)\, dx=f(g(x))$$

This is the basis of a basic integral substitution. If we let $g(x)=u \implies g'(x)\, dx=du$ we can change the above integral into

$$\int f'(u)\, du=f(u)=f(g(x))$$

Using this method, we let

$$f(x)=\exp(-x)$$ $$g(x)=u= \frac{x^2}{2} \implies x=\sqrt{2 u} \implies dx= \frac{1}{\sqrt{2u}}\, du$$

so the integral becomes

$$\int x\exp(-x^2/2)\, dx=\int \sqrt{2u}\cdot\exp(-u)\, \cdot\frac{1}{\sqrt{2u}}\, du=-\exp(-u)=-\exp(-\frac{x^2}{2})$$

share|cite|improve this answer

As $(\exp(-x^2/2))´=-x \exp(-x^2/2)$ we have \begin{eqnarray} \int_{0}^{\infty}x \exp(-x^2/2)dx &=& \lim_{\varepsilon\uparrow \infty}\int_{0}^{\varepsilon}x \exp(-x^2/2)dx \\ &=& \lim_{\varepsilon\uparrow \infty}[-\exp(-\varepsilon^2/2)]_{0}^{\varepsilon}\\ &=& \lim_{\varepsilon\uparrow \infty}( -\exp(-\varepsilon^2/2)+1 )\\ &=& 1. \end{eqnarray}

share|cite|improve this answer
This is a very unusual $\varepsilon$. Usually $\varepsilon \to 0$, but this one $\to \infty$. Good for it! – marty cohen Aug 21 '12 at 3:22

If you've reproduced the problem correctly, then you are correct and the solution key is incorrect.

As you said, if we set $f(x) = \exp(-x)$ and $g(x) = x^2 /2$, then the integrand is of the form $-f'(g'(x))\cdot g'(x)$, so we have by the (inverse) chain rule

$$ \int_0^\infty x \exp(-x^2 / 2) dx = \left [ -f(g(x)) \right ]_0^\infty = \left [ -\exp(x^2 /2) \right ]_0^\infty = 1$$

share|cite|improve this answer
@Calvin McPhail-Snyder Thank you for your answer. I started to doubt I've reproduced the problem correctly. Actually this problem is from Putnam exam in 1997. (A-2). Could you take a look at it? I still don't understand where I got it wrong. Here is a link. – Tengu Aug 21 '12 at 0:43
@DavidMitra Thanks. I already felt bad about posting this after your comment, but I would hope that I could at least get it right... – Calvin McPhail-Snyder Aug 21 '12 at 0:47

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.